Tanimbar Weaving Production in Enhancing the Economy of Namtabung Village, Selaru District, Tanimbar Islands Regency - Titisay, Antonia; Salakory, Melianus; Lasaiba, Mohammad Amin (Jurnal Pendidikan Geografi Unpatti, 2023)
Weavers are the primary process that converts natural and artificial spun yarn into cloth to be processed into finished goods. At the same time, the woven fabric results from human crafts on fabric made of thread, wood fiber, and sultan by inserting the weft transversely on the warp, namely the rows of threads attached longitudinally. This craft industry opened jobs for women who previously only followed their husbands in farming; now, they can work as craftsmen to help the family economy and increase family income. From the results of weaving, they get income to increase family income and be used to fulfill their daily needs. The objectives of this study are as follows: to determine the development of Tanimbar woven fabric production in improving the economy of the people of Namtabung Village, Selaru District, Tanimbar Island regency, and to determine the inhibiting factors in the manufacture of Tanimbar woven fabric to improve the economy of the people of Namtabung Village, Selaru District, Tanimbar Island regency with the production of woven fabrics. This type of research used in this writing uses the SWOT analysis method to determine strengths, Weaknesses, Opportunities, and Threats. This research was conducted in Namtabung Village, Selaru District, Tanimbar Island Regency. This research was conducted for one month, with the specified sample taken, 25% of the total population, namely as many as 30 people.